Pendidikan Inklusi Sebagai Perwujudan Sekolah Humanis Bermartabat Di Kota Kediri - Susilowati, Lia; Imtitsal Rasyidah, Umi (Lembaga Penelitian Universitas Pangeran Diponegoro Nganjuk, 2024)
Inclusive education facilitates and embraces student diversity as part of the implementation of dignified and humanistic education. This study concludes that: (1) The preparation for implementing inclusive education in Kediri City includes education systems and management, initial assessments, workshops/seminars, the provision of facilities and infrastructure, teacher development, and socialization; (2) The implementation of inclusive education covers classroom models, curriculum models, the role of educators, and the learning process; (3) The outcomes of inclusive education implementation include supervision by principals through regular monitoring, guidance from school supervisors, periodic evaluations by educational institutions, and the involvement of parents/guardians as educational partners. Inclusive education in the Dignified Excellent Elementary Schools of Kediri City aims to create an adaptive, participatory, and inclusive learning environment tailored to the diverse needs of students.